2020
DOI: 10.1103/physreva.101.013816
|View full text |Cite
|
Sign up to set email alerts
|

Modulational instability and frequency combs in whispering-gallery-mode microresonators with backscattering

Abstract: We introduce the first principle model describing frequency comb generation in a WGM microresonator with the backscattering-induced coupling between the counter-propagating waves. Elaborated model provides deep insight and accurate description of the complex dynamics of nonlinear processes in such systems. We analyse the backscattering impact on the splitting and reshaping of the nonlinear resonances, demonstrate backscattering-induced modulational instability in the normal dispersion regime and subsequent fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
1
43
0
1
Order By: Relevance
“…The generation of dark solitons or platicons by the free-running laser was found to be practically impossible due to the absence of the modulational instability (MI), so that the system remained in the cw solution during the scanning. In our earlier work we showed that the presence of the backward wave can induce MI [40]. In our opinion this fact in combination with nontrivial tuning curve in the SIL regime [see Fig.…”
Section: Normal Gvdmentioning
confidence: 77%
See 3 more Smart Citations
“…The generation of dark solitons or platicons by the free-running laser was found to be practically impossible due to the absence of the modulational instability (MI), so that the system remained in the cw solution during the scanning. In our earlier work we showed that the presence of the backward wave can induce MI [40]. In our opinion this fact in combination with nontrivial tuning curve in the SIL regime [see Fig.…”
Section: Normal Gvdmentioning
confidence: 77%
“…The field amplitudes are normalized to photon concentration using the same laser-referred coefficient to simplify the expressions. We modify accordingly the equation system for the SIL effect from [12], thus combining it with the results of [40] for the high-finesse microresonator and obtain the coupled mode equation system (CMES) [41] in the form…”
Section: Complete Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…These shifts are different for '+' and '−' waves. In the high repetition rate devices, the phase dependent four-wave mixing terms inside the XPM part of the Kerr response, |ψ ∓ | 2 ψ ± , oscillate with the fast rate ∼ 2D 1 [16][17][18]. If finesse F = D 1 /κ 1, then the fast oscillations can be disregarded and this is why the XPM nonlinearity in Eq.…”
mentioning
confidence: 99%